Implementation of Problem Based Learning With Play Money Media to Improve Arithmetic Understanding of Elementary School Students - Suwanda, Adhi; Sutopo, Yeri; Yuwono, Agus (International Journal of Education, Information Technology, and Others, 2025)
This study aims to improve the understanding of the concept of arithmetic operations of elementary school students through the application of Problem Based Learning (PBL) learning model assisted by toy money media. This study used a Classroom Action Research (PTK) design conducted in two cycles. The research subjects consisted of 30 fourth grade students who were selected by purposive sampling. Data were collected through written tests (pre-test and post-test), observations, and interviews. The results showed a significant increase in student understanding, with an average pre-test score of 60.3 increasing to 75.5 in the first cycle, and 88.7 in the second cycle. In addition, student activity in learning also increased from 65% in the first cycle to 85% in the second cycle. The PBL model with play money media proved to be effective in motivating students, increasing involvement in group discussions, and facilitating understanding of the concept of arithmetic operations in a real-life context. This study recommends the application of similar methods in other mathematics topics to support students' understanding and skills more broadly.